Development of Web-based Commerce Lapaksenggol.com as a Medium of Promotion and Marketing for SMEs in East Jakarta - Purwana, Dedi; Monoarfa, Terrylina Arvinta; Febrilia, Ika (Jurnal Pemberdayaan Masyarakat Madani (JPMM), 2023)
The situation during Covid-19 requires businesspeople to adapt to existing conditions and survive in an industry. It should be realized that not all SMEs have the same digital literacy, so it needs support from various parties to provide understanding and assistance to improve the skills of SMEs in utilizing digital platforms in business activities. The contribution of Lapaksenggol.com in community service activities to the Jakarta SMEs group (Jakpreneur), which is under the guidance of the East Jakarta Sub-Department of Trade, Industry, Cooperatives and SMEs is in its second year, where through this proposal, the team seeks to improve service quality by developing the service features of the Lapaksenggol.com website. The workshop was carried out for six months, starting from April to September 2022. Considering the Covid-19 pandemic, various activities will be implemented face-to-face (on the network) through Zoom. The results obtained from the socializations are the introduction of the Lapaksenggol.com marketplace and provided understanding to SMEs about the importance of doing social media advertising, managing finances in business activities, and introducing the SIAPIK application to support the business activities of SMEs in East Jakarta.